Characteristics of Studies Focusing on Vaccine Series Completion Among Children Aged 12–23 Months in Sub-Saharan Africa: A Scoping Review - Weiqi Li; Fabrice Sewolo; Andrew Aoun; Minyahil Tadesse Boltena; Amro Musad; Ann Lindstrand; Tobias Alfvén; Claudia Hanson; Ziad El-Khatib (Children)
Vaccine preventable diseases remain the leading causes of death among children in Sub-Saharan Africa. Background/Objectives: As vaccines provide the best possible protection only when all required doses are received, it is essential to understand how the published literature is designed and conducted regarding the completion of recommended childhood vaccine series for children aged 12–23 months in SSA. Methods: A comprehensive search was conducted across five databases (PubMed, Embase, CINAHL, Web of Science, and Google Scholar) to identify the relevant literature published between January 2000 through December 2023. Results: A total of 53 studies meeting the inclusion criteria were identified from the five databases. Over half of the studies used a cross-sectional design (n = 32, 60.4%), and less than half of the studies were conducted in Ethiopia (n = 23, 43.4%). The prevalence and associated factors of vaccination series completion were the most commonly explored topics in the literature. The most frequently reported factors associated with vaccine series completion included the caregiver’s education level, household wealth status, number of children under five in the household, knowledge of immunization, maternal education, place of residence, gender of the household head or decision maker, utilization of antenatal or postnatal care visits, place of delivery, distance to a healthy facility or travel time, and possession of a vaccination card. Conclusions: This scoping review identified methodological gaps in the published literature, including a lack of publications from many Sub-Saharan Africa countries and insufficient evidence on trends and inequalities in vaccine series completion. Future research on vaccine series completion is recommended to address these gaps.